Astrophysics and Space Science From X-Ray Binaries to Quasars: Black Holes on all Mass Scales - Maccarone, T. J.; Fender, R. P.; Ho, L. C.; SpringerLink (Online service) (Dordrecht : Springer Netherlands, 2005)
This volume brings together contributions from many of the world's leading authorities on black hole accretion. The papers within represent part of a new movement to make use of the relative advantages of studying stellar mass and supermassive black holes and to bring together the knowledge gained from the two approaches. The topics discussed here run the gamut of the state of the art in black hole observational and theoretical work-variability, spectroscopy, disk-jet connections, and multi-wavelength campaigns on black holes are all covered. Reprinted from ASTROPHYSICS AND SPACE SCIENCE, 300:1-3 (2005).
A unified model for black hole X-ray binary jets? -- On the relationship between the jets from X-ray binaries and AGN -- A transition in the accretion properties of AGN -- Jet-disc coupling in the accreting black hole XTE J1118+480 -- Are 3C 120 and other active galactic nuclei overweight microquasars? -- A fundamental plane of black hole activity: Pushing forward the unification scheme -- Magnetically dominated accretion flows (MDAFS) and jet production in the lowhard state -- Black hole systems seen at high spectral resolution: Inflow and outflow -- Black hole spin in AGN and GBHCs -- The Seyfert-liner galaxy NGC 7213: An XMM-Newton observation -- Observational effects of strong gravity -- Broad iron lines in AGN and X-ray binaries -- The evolution of black hole states -- Rapid X-ray variability of Seyfert 1 Galaxies -- Epicyclic frequencies derived from the effective potential: Simple and practical formulae -- X-ray periodicity in AGN -- Resonant oscillations of accretion flow and KHZ QPOS -- Comparing black hole and neutron star variability -- X-ray and radio monitoring of GX 339-4 and CYG X-1 -- Accretion in strong gravity: From galactic to supermassive black holes -- Low-luminosity accretion in black hole X-ray binaries and active galactic nuclei -- Exploring the jet/accretion flow relationship in low disk luminosity sources -- What can we learn from neutron star X-ray binaries$1 (Bjets? -- A unifying scheme for low-luminosity XRBs and AGN -- (3z(BLow-state(3y (Bblack hole accretion in nearby galaxies -- Present evidence for intermediate mass black holes in ULXs and future prospects -- Finding faint intermediate-mass black holes in the radio band -- Formation and evolution of intermediate mass black hole X-ray binaries -- TeV gamma rays from the galactic center direct and indirect links to the massive black hole in Sgr A* -- AGNS and microquasars as high-energy ?-ray sources -- Large scale jets in microquasars -- Is GRS 1915+105 a microquasar?.s
Keywords: Physics; Gravitation; Observations, Astronomical; Astronomy -- Observations; Astrophysics; Space sciences; Particle acceleration; Atomic structure; Molecular structure; Spectra; Physics; Astrophysics and Astroparticles; Astronomy, Observations and Techniques; Extraterrestrial Physics, Space Sciences; Classical and Quantum Gravitation, Relativity Theory; Particle Acceleration and Detection, Beam Physics; Atomic/Molecular Structure and Spectra; Electronic books